Combined Maternal and Post-Hatch Dietary Supplementation of 25-Hydroxycholecalciferol Alters Early Post-Hatch Broiler Chicken Duodenal Macrophage and Crypt Cell Populations and Their Mitotic Activity - Leiva, Samuel F.; Avila, Luis P.; Abascal-Ponciano, Gerardo A.; Flees, Joshua J.; Sweeney, Kelly M.; Wilson, Jeanna L.; Starkey, Jessica D.; Starkey, Charles W. (Frontiers in Veterinary Science, 2022)
Previous work has demonstrated that maternal supplementation of the circulating metabolite of vitamin D3 (D3), 25-hydroxycholecalciferol (25OHD3) enhances immunocompetence of broiler chick offspring. In post-hatch broiler diets, 25OHD3 has been shown to affect intestinal morphology and improve immune status of broilers. An experiment with a 2 × 2 factorial treatment arrangement was conducted to assess effects of combining maternal (MDIET) and post-hatch (PDIET) dietary 25OHD3 inclusion on duodenal crypt and macrophage cell populations and mitotic activity in young broiler chickens. All diets were formulated to provide 5,000 IU of vitamin D. Broiler breeder hens were offered 1 of 2 MDIET: 5,000 IU D3 per kg of feed (MCTL) or 2,240 IU of D3 + 2,760 IU of 25OHD3 per kg of feed (M25OHD3) from wk 25 to 41. Male broiler offspring (n = 480) hatched from eggs collected during wk 41 of breeder age were allotted in raised floor pens (4 birds per pen from d 0 to 7 and individually allotted from d 8 to 21). Chicks were fed 1 of 2 PDIET (starter d 0 to 21): 5,000 IU D3 per kg of feed (PCTL) or 2,240 IU D3 + 2,760 IU 25OHD3 (P25OHD3). DUO samples (n = 12 birds per treatment per d) were collected on d 3, 6, 9, 12, 15, 18, and 21 for cryohistological and immunofluorescence analysis to facilitate enumeration of total macrophages, CD80+ macrophages (Pro-inflammatory macrophages), and mitotically active cells (BrdU+) to calculate the proportion of proliferating cells (PPC) per duodenal crypt. Bird age impacted crypt PPC with the greatest PPC per duodenal crypt observed on d 3 and 9, and the lowest PPC per crypt observed on d 21 (P < 0.0001). Broilers from the M25OHD3:PCTL treatment had a greater PPC (P = 0.002) than birds from the MCTL:PCTL treatment at d 3. An interaction among MDIET and PDIET was observed for proliferating macrophages at d 21 (P = 0.029) where M25OHD3:P25OHD3 birds had more proliferating macrophages than M25OHD3:PCTL-fed birds. These results indicate that combined MDIET and PDIET 25OHD3 supplementation may alter early post-hatch duodenal development and innate immunity.